Approach to the diagnosis of skeletal dysplasias: Experience at a center with limited resources. Issue 9 (24th May 2016) - Kumar, Manisha; Thakur, Seema; Haldar, Arunima; Anand, Rama
ABSTRACT: Purpose: A fetus with skeletal disorder poses diagnostic challenges in a resource‐poor setting with limited management options. The objective of the study was to develop a step‐by‐step approach for the diagnosis of skeletal dysplasia in light of the limited resources available. Methods: An algorithmic approach was used. The assessment for lethality was the first step, followed by the evaluation for fractures. In cases without evidence of fracture, severe constriction of thorax or associated polydactyly were searched for. In cases without severe thoracic constriction, the severity of micromelia was evaluated. After delivery, fetal examination was done to ascertain the etiology. Results: During the 6‐year period, 41 cases with shortened long bones were fully evaluated. Lethality was suspected in 30 cases. Fracture and beading were present in eight cases, and severe thoracic constriction with polydactyly was observed in seven cases. Mild micromelia was seen in 19 cases and severe micromelia in 7 cases. Among lethal skeletal dysplasias, thanatophoric dysplasia was most common (six cases). Among nonlethal skeletal dysplasias, achondroplasia was seen in eight cases. Conclusions: Lethality of skeletal dysplasia could be predicted on prenatal ultrasound with 100% accuracy. The step‐by‐step approach was helpful to characterize skeletal dysplasias. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44 :529–539, 2016